Multi-wavelength anomalous diffraction de novo phasing using a two-colour X-ray free-electron laser with wide tunability - Alexander Gorel (Nature Portfolio, 2017)
X-ray free-electron lasers produce bright femtosecond X-ray pulses. Here, the authors use a two-colour X-ray free-electron laser beam for simultaneous two-wavelength data collection and show that protein structures can be determined with multiple wavelength anomalous dispersion phasing, which is important for difficult-to-phase projects.